1996
DOI: 10.1111/j.1365-2125.1996.tb00172.x
|View full text |Cite
|
Sign up to set email alerts
|

The tolerability and pharmacokinetics of the novel antimigraine compound 311C90 in healthy male volunteers

Abstract: 1 311C90 is a novel and selective agonist at 5-HTID receptors, with central and peripheral actions, currently in development for the acute oral treatment of migraine. 2 The pharmacokinetic and tolerability profiles of single oral doses from 1-50 mg 311C90 were investigated in 12 healthy male volunteers in a double-blind, placebo-controlled, dose-escalating study. 3 311C90 was well tolerated with most adverse experiences of mild and transient nature. 4 Absorption was rapid with dose-independent kinetics. Median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 7 publications
11
32
2
Order By: Relevance
“…There was, however, little information on the reason for this. Interestingly, Seaber et al (1996) reported that the metabolite, N-demethylated There was also a significant difference (p < 0.001) between the IC 50R/S for R-inhibiting S-zolmitriptan and the IC 50S/R for S-inhibiting R-zolmitriptan (Fig. 4).…”
Section: Concentrationmentioning
confidence: 85%
“…There was, however, little information on the reason for this. Interestingly, Seaber et al (1996) reported that the metabolite, N-demethylated There was also a significant difference (p < 0.001) between the IC 50R/S for R-inhibiting S-zolmitriptan and the IC 50S/R for S-inhibiting R-zolmitriptan (Fig. 4).…”
Section: Concentrationmentioning
confidence: 85%
“…However, this dose is not clinically available or used in practice. 4,40 Finally, for all formulations, Zolmitriptan's elimination half-life is approximately 3 hours. 4,14,33 Pharmacokinetic differences in the ictal and interictal migraine periods…”
Section: Metabolism and Eliminationmentioning
confidence: 99%
“…Supine blood pressure, heart rate and blood sampling (for the determination of zolmitriptan and metabolites) were performed immediately before each test session. Plasma concentrations of zolmitriptan and its major metabolites were determined by reverse-phase high performance liquid chromatography with ßuorescence detection (Seaber et al 1996). Adverse experiences reported spontaneously and in response to an open question were recorded.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Zolmitriptan also has a good pharmacokinetic proÞle, with rapid absorption following oral administration and dose proportional plasma concentrations (Seaber et al 1996). The absolute oral bioavailability is approximately 45 % and the half-life is 2.53 h.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation